An online vignette experiment on stigma and help-seeking attitudes towards five mental health problems in adolescents and emerging adults - Diana Lemmer; Markus Moessner; Nicolas Arnaud; Harald Baumeister; Agnes Mutter; Sarah-Lena Klemm; Elisa König; Paul Plener; Christine Rummel-Kluge; Rainer Thomasius; Michael Kaess; Stephanie Bauer (Scientific Reports)
Abstract Public attitudes vary across mental health (MH) problems. However, research on young people and certain MH conditions is limited. This online-experiment examined stigma and potential help-seeking among 554 adolescents and emerging adults aged 14–29 years towards generalized anxiety disorder, depression (DEP), bulimia nervosa (BN), non-suicidal self-injury (NSSI), and problematic alcohol use (ALC). Participants were randomized to a video vignette depicting one of the five MH problems. Attitudes were measured with the Universal Stigma Scale (subscales: “blame/ personal responsibility” and “impairment/ distrust”) and the General Help Seeking Questionnaire assessing the likelihoods of seeking professional, informal, and no help for the respective MH problem. Data were analysed using Kruskal-Wallis and Bonferroni-corrected Dunn’s tests. Compared to all of the other conditions, ALC was the most stigmatized. Furthermore, ALC was more likely to prompt any help-seeking as compared to DEP, BN, and NSSI, and professional help-seeking in comparison to DEP. BN elicited more blame than DEP, whereas the reverse pattern emerged for distrust. However, this sample generally held positive MH attitudes. The results highlight the importance of addressing disorder-specific stigma and may inform the development of targeted anti-stigma and help-seeking campaigns. Trial registration: This study has been registered at the German Clinical Trials Register (www.drks.de) on September 23rd, 2020 https//drks.de/search/de/trial/DRKS00023110 #DRKS00023110.